Design of Multi-liquid Mixing Control System Based on S7-300. Issue 1 (1st March 2022) - Ji, Jun; Huang, Dun-Hua; Xing, Fei-Fei
Abstract: This article introduces the application scenarios of a variety of liquid mixing control devices, studies the analog and function knowledge points involved in the control system, analyzes the control requirements, and designs the program.